Analisa Transparansi APBDdes Sebelum Dan Saat Pandemi - Vinsensius Bima; Imelda Sinaga; Victoria Ari Palma Akadiati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The motivation of this research is to determine the financial performance of the APBDes in Keputran Village so that it can provide information in making decisions on the results of the analysis during this pandemic. The data analysis method used is descriptive quantitative. Research shows that the financial performance of BUMDes in Keputran Sari Village for 2 years seen from the effective level shows that in 2019 before the pandemic it showed quite effective results and in 2020 during the pandemic the effectiveness level was also quite effective. The results of the calculation of the efficiency level for 2 years get results that are not yet efficient, so it needs to be improved again in utilizing the budget they have. The results of the calculation of economic rates for 2 years get very economical results. For the conclusion that the APBDes financial performance in the Keputran village is classified as good enough, it can be seen from the three indicators that only 1 of the 3 variables does not match the results.